2017
DOI: 10.3174/ajnr.a5160
|View full text |Cite
|
Sign up to set email alerts
|

Proton Chemical Shift Imaging Study of the Combined Antiretroviral Therapy Impact on Neurometabolic Parameters in Chronic HIV Infection

Abstract: The impact of combined antiretroviral therapy on the process of neuronal loss and dysfunction in chronic HIV infection appears to be suboptimal in successful peripheral suppression of viral replication. Spectroscopic imaging might be a useful tool for monitoring the effects of different combined antiretroviral therapy regimens on brain metabolite ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…When comparing HIV-positive patients of different age groups with age-matched healthy subjects, the results of our study showed that NAA/Cr ratios were significantly decreased in chronically infected, virally suppressed HIV-positive subjects, compared to healthy controls. This has also been observed in previous spectrosopic studies ( Bairwa et al, 2016 ; Boban et al, 2017 ). In HIV-positive subjects, the presence of HIV infection was the strongest contributor to this decline, followed by age.…”
Section: Discussionsupporting
confidence: 90%
“…When comparing HIV-positive patients of different age groups with age-matched healthy subjects, the results of our study showed that NAA/Cr ratios were significantly decreased in chronically infected, virally suppressed HIV-positive subjects, compared to healthy controls. This has also been observed in previous spectrosopic studies ( Bairwa et al, 2016 ; Boban et al, 2017 ). In HIV-positive subjects, the presence of HIV infection was the strongest contributor to this decline, followed by age.…”
Section: Discussionsupporting
confidence: 90%
“…were the first to report a progressive reduction of the NAA level in HIV-positive subjects in a short follow-up period (three to eight months) 15 . Furthermore, based on later longitudinal studies, long-term control of both processes, neuroinflammation and consequent neurodegeneration, seemed to be suboptimal despite cART and good peripheral viral suppression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies showed several important characteristics of brain injury in chronic HIV infection: global parenchymal reduction (loss of both gray and white matter), changes in the neurometabolic profile, and disturbances in neurotransmission (10,11). Studies based on magnetic resonance spectroscopy (MRS) showed ongoing inflammation and progressive neurodegeneration, even in virally suppressed, neurologically asymptomatic HIV-infected individuals with normal findings on conventional magnetic resonance imaging (MRI) (10,12). MRS is a non-invasive diagnostic modality that enables in vivo monitoring of subtle changes in the neurometabolic profile and has a potential role in the evaluation of cART efficacy in the CNS compartment.…”
Section: Introductionmentioning
confidence: 99%